2016
DOI: 10.1186/s13075-016-1152-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeated decrease of CD4+ T-cell counts in patients with rheumatoid arthritis over multiple cycles of rituximab treatment

Abstract: BackgroundSignificant peripheral blood CD4+ T-cell depletion has been observed after a first cycle of rituximab, a monoclonal antibody directed against the CD20 antigen, which is currently used in rheumatoid arthritis. Of note, an absence of CD4+ T-cell decrease has been observed in non-responders. Herein, we describe CD4+ T-cell changes over repeated cycles of rituximab and their relationship with clinical outcomes.MethodsPatients with rheumatoid arthritis who started rituximab between July 2007 and July 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
(20 reference statements)
0
20
0
1
Order By: Relevance
“…A follow‐up study by the same group was published in 2016 where patients received up to seven cycles of treatment during the study period. Mean CD4 + T‐cell counts were above the upper limit of the reference range before each rituximab infusion and repeatedly reached the reference range at 6 months (and/or 3 months) post infusion . In patients with RA, repeated post‐treatment decrease in CD4 + T‐cell counts occurred over successive cycles of rituximab .…”
Section: Do Anti‐cd20 Antibodies Cause Cd4+ T Lymphopenia?mentioning
confidence: 95%
See 1 more Smart Citation
“…A follow‐up study by the same group was published in 2016 where patients received up to seven cycles of treatment during the study period. Mean CD4 + T‐cell counts were above the upper limit of the reference range before each rituximab infusion and repeatedly reached the reference range at 6 months (and/or 3 months) post infusion . In patients with RA, repeated post‐treatment decrease in CD4 + T‐cell counts occurred over successive cycles of rituximab .…”
Section: Do Anti‐cd20 Antibodies Cause Cd4+ T Lymphopenia?mentioning
confidence: 95%
“…Mean CD4 + T‐cell counts were above the upper limit of the reference range before each rituximab infusion and repeatedly reached the reference range at 6 months (and/or 3 months) post infusion . In patients with RA, repeated post‐treatment decrease in CD4 + T‐cell counts occurred over successive cycles of rituximab . In minimal change nephrotic syndrome, remissions after rituximab therapy were associated with significant decrease in the frequency of CD4 + follicular helper T cells .…”
Section: Do Anti‐cd20 Antibodies Cause Cd4+ T Lymphopenia?mentioning
confidence: 96%
“…The incidence rates of HZ were higher in rituximab (3.9 per 100 patient-years) and abatacept (8.5 per 100 patient-years) period compared to cDMARDs period. Several studies have been reported that rituximab induces T cell depletion, mainly of CD4+ T cells in patient with RA [21,22]. Based on these results, decreased of CD4+ T cell counts after rituximab therapy would be made and consequently might affect to RA patients to be more vulnerable to HZ.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, all patients showed a relevant CD4-lymphopenia (all patients < 200/µL) with low levels of naïve CD4 cells (< 10% in all patients). Of note, while hypogammaglobulinemia is an expected and known adverse event following RTX treatment, it has been reported that RTX treatment can induce CD4-lymphopenia [26][27][28].…”
Section: Discussionmentioning
confidence: 99%